Kartezjański obraz Boga i nieba. Kontrowersje - Drozdowicz, Zbigniew (Humaniora. Czasopismo Internetowe, 2022)
One of the more controversial issues was and still is the picture of God and heaven as taken by the philosophers. Today, without a great effort we may be able to find such who openly claim that there is no God and the belief his in existence is (to use the term by R. Dawkins) a human “delusion.” However heaven does exist but it is a part of the natural world. In the times of Descartes such philosophers and scholars also did occur. Nevertheless they were not numerous and so unimportant that we may ignore them. Descartes wasn’t one of them. His philosophy was acknowledged and still is by many specialists in the philosophical tradition as groundbraking and influential. Since this very moment of its emergence deep controversies had arised among others by the issue of carthesian picture of God and heaven. In these remarks I do recall several of them. My general thesis can be summed up by the stand point that in the carthesian system God had been assigned with an important but not central role. The central role had been reserved for sich a man that wants and is able to use his/hers own intellect.